IMPLEMENTASI MODEL PEMBELAJARAN RUMAH BILANGAN UNTUK MENINGKATKAN KEMAMPUAN OPERASI HITUNG PENGURANGAN PADA SISWA KELAS 1 SD BINEKAS - Ghina Zakiya; Happy Karlina Marjo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop and implement the Number House learning model to improve subtraction operation skills in first-grade students at SD Binekas Bandung. The implementation procedure was carried out through three meetings focusing on subtraction without regrouping, subtraction with regrouping, and application in word problems. The research method used a descriptive qualitative approach with 25 first-grade Gumujeng students as research subjects. The results showed an increase in conceptual understanding in 85% of students in completing subtraction operations using the Number House model, especially in the second and third meetings. The obstacles faced were difficulties of some students in understanding the place value concept during the regrouping process, but these could be overcome with intensive assistance and the use of more concrete visual media. As a follow-up, it is suggested to develop the Number House learning media in the form of interactive games and apply this method to other arithmetic operations to build a strong mathematical foundation for early grade students. Keywords: Number House Model, Subtraction Operation, Elementary School, Place Value, Learning Media